Securing e-learning environment: A study of security awareness and behavior of user - Wan Nurul Safawati, Wan Manan; Mazlina, Abdul Majid; Hasmanizam, Abdul Majid; Mohd Izham, Ibrahim (American Scientific Publishers, 2017)
Rapid development of the Internet and technology has shifted the education environment from traditional classroom environments to a state of the art technology-based environment. The term e-learning describes the situation where teaching and learning activities are done not only in classrooms, but virtually using the Internet. Users of e-learning system can access their course materials, lecture notes, quizzes, exams and discussion rooms through the Internet everywhere and at any time. While the technology makes the access easy, there are issues, particularly related to security that need to be concerned. The challenges in securing an e-learning system do not fall on the system itself, or the infrastructure. It is user awareness and behavior that give opportunities to the attackers to compromise the system. Low security awareness leads to poor behavior, which results to system compromise. This paper discusses security awareness and behavior of e-learning users as the main focus to secure the overall e-learning environment. Furthermore, this paper reviews the existing research explaining e-learning environment, security, threats and issues.